Nepalese psychiatric patients with armed-conflict related stressors - Shakya, DR; Lamichhane, N; Shyangwa, PM; Shakya, R (Health Renaissance, 2011)
Introduction: Psychiatric disorders have long been associated with bio-psycho-social factors. The relationship of stressful events with the etiology and the course of mental illness have similarly been much considered. Among different types of conflicts, armed political is the one under which many countries including Nepal have been reeled directly. This study aims to evaluate the psychiatric morbidity profile of patients with the stressors related to the then ongoing political conflict in Nepal. Methods: This is a hospital based, descriptive study with convenient sampling method carried out in Department of Psychiatry, B P Koirala Institute of Health Sciences. The diagnosis was based on Chapter V (F) of ICD- 10. Results: Among 50 subjects, there were 36 males and 14 females. More than half of the subjects were of productive age. During the war period, more than half had been affected directly; physically and or psychologically while other halves indirectly. Nearly all subjects had biological/ somatic symptoms, followed by anxiety and psychotic symptoms. Two cases (4%) presented with attempted suicide. Affective disorders were the most common diagnosis among the subjects with conflict related stressors. Conclusion: Many of the mentally ill people had significant political stressor in current day Nepal. Hence, as described in the literature, it is a risk factor. Keywords: armed conflict; conflict related stressor; psychiatric disorder; Nepal. DOI: http://dx.doi.org/10.3126/hren.v9i2.4975 Health Renaissance 2011: Vol.9 (No.2): 67-72